Mo. Rev Stat 306, § 4 (1845) - (:unkn) unknown (My University, 1844)
An Act To Restrain Intercourse With Indians, § 4: No person shall sell, exchange or give, to any Indian, any horse, mule, gun, blanket, or any other article or commodity whatever, unless such Indian shall be traveling through the state, and leave a written permit from the proper agent, or under the direction of such agent in proper person.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES